Desenvolvimento e fabricação de penetradores para avaliação da resistência ao desgaste abrasivo de polímeros protetores de risers - Magalhães, Luciano da Rocha (2013)
Deep water oil production imposes several challenges to the oil companies. One of the greatest difficulties is related to the damages that the flexible riser pipes are subjected. These pipes conduct the produced oil to the platform. They are also used to inject water in the well in order to recover its production capacity. Among the damages mentioned, its worth to mention the abrasive wear that takes place at the touchdown point (TDP). In order to reduce this tribological degradation, PU coats have been used at the TDP region. Considering the diversity of PU that can be used in this application, it is highly desired that the PU plaques quality are controlled before its installation. Based on this demand, a portable apparatus was designed and constructed in the Laboratory for Friction and Wear at the Federal University of Uberlândia to simulate the tribological interactions between the riser pipe and the sea bed. So this work aims to produce WC-Co indenter for this test apparatus. To accomplish that, the following steps were proposed: a) equipment preparation for wear tests; b) determination of test parameters (cycle number and load) through a full factorial design; c) geometric and dimensional control of the indenters before and after machining processes; d) realization of wear tests before and after machining the indenters; e) machining of indenters using honing and lapping and f) analysis of the improvements achieved on the wear results. The results obtained allowed the following conclusions: 1) the proposed machining processes and parameters for are appropriate to manufacture the indenter In accordance with their selected dimensional and geometric tolerances. Roughness values of about 2.0 μm has been reduced by at least 60%, while for values lower than 2.0 μm this reduction was at least 33%, and 2) abrasion tests using the new indenters provide more precise and reliable results.